Efikasi Diri dan Kecerdasan Emosional dengan Perilaku Kewargaan Organisasi pada Pramugari Pramugara Maskapai X - Prasetyaningrum, Ketut Ayumas; Simarmata, Nicholas (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
Flight attendant is one of occupations that engages on service industry in airline sector. X Airlines is one of the airlines in Indonesia. Flight attendants’ duty includes giving service and ensuring the safety of passengers during an airline flight. With such high risk job, flight attendants are expected to fully commit to their work, in specifically to work voluntary. The voluntary behaviour is labelled as Organizational Citizenship Behaviour (OCB), which is performed outside the flight attendant job description, for instance helping out fellow co-workers and keeping their responsibility well. Flight attendants should possess Self-Efficacy and Emotional Intelligence, in order to develop Organizational Citizenship Behaviour (OCB). Therefore, this study aims to examine the correlation between Self-Efficacy and Emotional Intelligence with Organizational Citizenship Behaviour of Flight Attendants of X Airlines.This study was a quantitative correlational research. The subjects of the study were 81 senior and junior flight attendants of X Airlines, aged 18 at the least, possessing as a minimum a high school/vocational school diploma or equivalent, working for minimum 6 months, and the employment status must be permanent employee, contract employee, and outsourcing employee. The reliability scale of efficacy was 0,881, the reliability scale of emotional intelligence was 0,873, and the reliability scale of Organizational Citizenship Behaviour was 0,901. According to the hypothesis testing with multiple regression analysis, the significance level resulted in 0,000 (p<0,01). The level meant there was a correlation between Self-Efficacy and Emotional Intelligence with Organizational Citizenship Behaviour of Flight Attendants of X Airlines. The effective variable of Self-Efficacy and Emotional Intelligence contributing to Organizational Citizenship Behaviour was 20,7%, meanwhile, the 79,3% ones derived from other factors except Self-Efficacy and Emotional Intelligence.Keywords: Self-Efficacy, Emotional Intelligence, Organizational Citizenship Behaviour, Flight Attendants of X Airline.